STUDYING OF THE FACTORS INFLUENCING ON FORMATION OF THE CONGENITAL MALFORMATIONS OF THE NEWBORNS - Маисеенко, Дмитрий Александрович; Галактионова, Марина Юрьевна; Шурова, Оксана Амрихудовна; Капитонов, Владимир Федорович; Полонская, Ольга Викторовна (Mother and Baby in Kuzbass, 2017)
Results of researches showed that most of the women who gave birth to children with malformations was made multiparas (three and more then three labour) by the women, active reproductive age consisting in repeated marriage, in most cases regularly visiting female consultation, who passed triple ultrasonic screening. More than a half of women had ekstragenital diseases, including infectious. Among newborns with malformations, more than in half of percent of cases is congenital heart disease.
Keywords: pregnancy; screening; delivery; congenital development defect; infants